Aspek Implementasi Monitoring Suhu Ruangan Kelas Perkuliahan Berbasis Wireless Sensor Network Pada Bangunan Fakultas Teknik Universitas Riau - Santi R Sipayung; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The uneven indoor temperatures at a high rise building to be one factor uncomfortable to do the activity. It became one of the problems. Uneven temperatures in certain parts, the people in the room did not feel the temperature generated by the air conditioning so it does not feel comfortable. With the development of Wireless Sensor Network can be apply the distribution of the resulting temperature in a room. To get good performance we conducted studies sensor placement and selection protocols. So through this study will be submitted studies to gain a temperature equalization by using wireless sensor networks in buildings C faculty of engginering.Keywords : Wireless Sensor Networks, peer to peer, directed diffusion